Crack density in bloodstains. Issue 24 (16th June 2020) - Choi, Junhee; Kim, Wonjung; Kim, Ho-Young
Abstract : This work presents a theoretical framework to understand the crack density of bloodstains by modeling whole blood as a suspension of binary size colloid particles. Abstract : We construct a theoretical framework to understand the crack density of bloodstains by modeling whole blood as a suspension of binary size colloid particles. Our analysis based upon theories of soft capillarity and porous flows explains the observed increase of the crack density with increase of blood viscosity and decrease of environmental humidity. The results have direct implications on forensic science and medical diagnosis.